A Study of Domestic Violence and Marital Adjustment on Disturbed snd Non-disturbed Married Couples - Singh, Kapoor; Bargujjar, Monika; Kumar Behmani, Rakesh (International Journal of Psychosocial Rehabilitation, 2021)
Introduction:A marriage is a bond that exists between a man and woman abide by law and customs prevailing in the society. In ancient times, problems faced in marital life could be seen less because either the husband or wife had a complete devotion to each other or conclusive thinking. The connection between domestic violence and marital adjustment controversial and notclear-cut. Methods:Now the present study sheds further light on the relationship between domestic violence and marital adjustment (in the form of disturbed and non-disturbed married couples) among couples in four district (Sirsa,Fatehabad,Hisar and Bhiwani) of Haryana (India) that is previously untested. Revised dyadic adjustment scale and revised conflict tactics scale was used for data collection. A total of 400 farmers were selected and analyzed using the F test, and describing using two way annova. Results:Findings reveal that non-disturbed couples shows a higher score and significant relationship in comparison to disturbed married couples on consensus, satisfaction, cohesion with others, on revised dyadic adjustment scale. Overall, Finding reveals that family type was significantly associated with gender difference among non-disturbed and disturbed married couples. Conclusion:This research gives insight and helpful for counselors to understand the perception and mindset of married couples about wealth.